Evaluation of Entomopathogenic Nematode Isolates against Subterranean Termites under Laboratory and Field Conditions [version 3; peer review: 2 approved, 1 approved with reservations] - Fikremariam Yimer; Teshale Daba Dinka; Tariku Tesfaye Edosa; Belay Feyisa; Belay Abate Gutema; Dawit Melisie Achlehum (F1000Research)
Background Termites are a major insect pest affecting agricultural production and woody materials. They cause severe devastation in the ecosystem, and lead to bare soil. This phenomenon causes the soil to become difficult to plow, which in turn leads to a reduction in the productivity of crops. It can cause 100 % yield losses based on crop types, level of the damage, and size of its populations. To manage this pest, different management options have been evaluated in Ethiopia. While insecticide usage is the dominant option, less attention has been given to Entomopathogenic Nematode (EPN) based management options. Therefore, this research was initiated to screen locally collected EPN isolates and evaluate promising isolates under field conditions on maize crop. Methods 37 EPN isolates were screened under laboratory condition, while two isolates were evaluated at field condition. The screening of EPN isolates was laid out in a completely randomized design, and the field evaluation used a completely randomized block design, and treatments were replicated thrice. Mortality of insect, damaged root, stem, cob, damage severity, foraging termites, and yield of the crop data were collected. Results The study indicated that all screened EPN isolates caused mortality on termites under laboratory conditions. The isolates achieved complete mortality of the insect pest within 12 days of exposure. The finding indicated that AEH and S#50 were the more pathogenic and virulent isolates on termites under laboratory conditions and taken to field study. The S#50 isolate was most pathogenic and reduced the infestation and severity of the insect pest on the maize crop under field conditions. Conclusions This result showed that the entomopathogenic nematode isolates have the potential to manage subterranean termites in the maize field. Future studies should be based on collection of local isolates and develop a full package for the virulent isolates.